Synergy of GSK-J4 With Doxorubicin in KRAS-Mutant Anaplastic Thyroid Cancer - Lin, Bo; Lu, Bing; Hsieh, I-yun; Liang, Zhen; Sun, Zicheng; Yi, Yang; Lv, Weiming; Zhao, Wei; Li, Jie (Frontiers in Pharmacology, 2020)
Background Anaplastic thyroid cancer is the most aggressive thyroid cancer and has a poor prognosis. At present, there is no effective treatment for it. Methods Here, we used different concentrations of GSK-J4 or a combination of GSK-J4 and doxorubicin to treat human Cal-62, 8505C and 8305C anaplastic thyroid cancer cell lines. The in vitro experiments were performed using cell viability assays, cell cycle assays, annexin-V/PI binding assays, Transwell migration assays and wound-healing assays. Tumor xenograft models were used to observe effects in vivo. Results The half maximal inhibitory concentration (IC50) of GSK-J4 in Cal-62 cells was 1.502, and as the dose of GSK-J4 increased, more anaplastic thyroid cancer cells were blocked in the G2-M stage. The combination of GSK-J4 and doxorubicin significantly increased the inhibitory effect on proliferation, especially in KRAS-mutant anaplastic cancer cells in vivo (inhibition rate 38.0%) and in vitro (suppresses rate Fa value 0.624, CI value 0.673). The invasion and migration abilities of the KRAS-mutant cell line were inhibited at a low concentration (p< 0.05). Conclusions The combination of GSK-J4 with doxorubicin in KRAS-mutant anaplastic thyroid cancer achieved tumor-suppressive effects at a low dose. The synergy of the combination of GSK-J4 and doxorubicin may make it an effective chemotherapy regimen for KRAS-mutant anaplastic thyroid cancer.